pH-Sensitive Gold Nanorods for Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) Delivery and DNA-Binding Studies - Eleni Zygouri; Vlasoula Bekiari; Georgios Malis; Nikos K. Karamanos; Christos Koutsakis; George Psomas; Vassilis Tangoulis (Molecules, 2023)
A facile experimental protocol for the synthesis of poly(ethylene glycol)-modified (PEGylated) gold nanorods (AuNRs@PEG) is presented as well as an effective drug loading procedure using the non-steroidal anti-inflammatory drug (NSAID) naproxen (NAP). The interaction of AuNRs@PEG and drug-loaded AuNRs (AuNRs@PEG@NAP) with calf-thymus DNA was studied at a diverse temperature revealing different interaction modes; AuNRs@PEG may interact via groove-binding and AuNRs@PEG@NAP may intercalate to DNA-bases. The cleavage activity of the gold nanoparticles for supercoiled circular pBR322 plasmid DNA was studied by gel electrophoresis while their affinity for human and bovine serum albumins was also evaluated. Drug-release studies revealed a pH-sensitive behavior with a release up to a maximum of 24% and 33% NAP within the first 180 min at pH = 4.2 and 6.8, respectively. The cytotoxicity of AuNRs@PEG and AuNRs@PEG@NAP was evaluated against MCF-7 and MDA-MB-231 breast cancer cell lines. The development of AuNRs as an efficient non-steroidal anti-inflammatory drugs (NSAIDs) delivery system for chemotherapy is still in its infancy. The present work can shed light and inspire other research groups to work in this direction.